Passive income lures people to invest in get-rich-quick schemes - New Sabah Times English, (KK) (New Sabah Times, 2016)
KOTA BAHARU: Earning passive income without having to lift a finger has caused many to be easily deceived into joining get-rich-quick schemes without thinking of the risks that await them.